Anti-viral activity of culinary and medicinal mushroom extracts against dengue virus serotype 2: an in-vitro study - Kavithambigai Ellan; Ravindran Thayan; Jegadeesh Raman; Kazuya I. P. J. Hidari; Norizah Ismail; Vikineswary Sabaratnam (BMC, 2019)
Abstract Background Dengue is a mosquito-borne viral infection that has become a major public health concern worldwide. Presently, there is no specific vaccine or treatment available for dengue viral infection. Methods Lignosus rhinocerotis, Pleurotus giganteus, Hericium erinaceus, Schizophyllum commune and Ganoderma lucidium were selected for evaluation of their in-vitro anti-dengue virus serotype 2 (DENV-2) activities. Hot aqueous extracts (HAEs), ethanol extracts (EEs), hexane soluble extracts (HSEs), ethyl acetate soluble extracts (ESEs) and aqueous soluble extracts (ASEs) were prepared from the selected mushrooms. The cytotoxic effects of the extracts were evaluated by the MTT assay. The anti-DENV-2 activities of the extracts were evaluated in three different assays: simultaneous, attachment and penetration assays were perfomed using plaque reduction assays and RT-qPCR assays. The effect of the addition time on viral replication was assessed by the time of addition assay, and a virucidal assay was carried out to evaluate the direct effect of each mushroom extract on DENV-2. The chemical composition of glucans, and the protein and phenolic acid contents in the extracts were estimated. Results We found that the HAEs and ASEs of L. rhinocerotis, P. giganteus, H. erinaceus and S. commune were the least toxic to Vero cells and showed very prominent anti-DENV2 activity. The 50% inhibitory concentration (IC50) values of the ASEs ranged between 399.2-637.9 μg/ml, while for the HAEs the range was 312.9-680.6 μg/ml during simultaneous treatment. Significant anti-dengue activity was also detected in the penetration assay of ASEs (IC50: 226.3-315.4 μg/ml) and HAEs (IC50: 943.1-2080.2 μg/ml). Similarly, we observed a marked reduction in the expression levels of the ENV and NS5 genes in the simultaneous and penetration assays of the ASEs and HAEs. Time-of-addition experiments showed that the highest percent of anti-DENV2 activity was observed when the mushroom extracts were added immediately after virus adsorption. None of the extracts exhibited virucidal effect. Chemical composition analysis showed that the major components in the mushroom HAEs and ASEs were glucan (beta D-glucan) and proteins, however, there was no significant correlation between the anti-dengue activity and the concentration of glucans and proteins. Conclusion These findings demonstrated the potential of mushroom extracts as anti-dengue therapeutic agents with less toxic effects.